Characteristics of urban housing units and their relation to the economic and social characteristics of their residents - A field study on the city of Mosul - Mumtaz Hazem al-Doji (Iraqi Journal of Architecture and Planning, 2009)
Iraqi cities have a rapid growth in their urban area with explosive populationincrease. This growth is accompanied with advent of various residential pattems. Thephenomenon is conspicuously explicit in Mosul as the major urban center in the northregion of Iraq.The hypothesis which states that residential pattems -by means of their physicalfeatures and location within urban area- are correlated with the occupants'characteristics including demographic, socio-economic, ethnic, cultural . . etc. isadopted and to be tested in order to determine the nature and scope ofthis relationshipin Mosul.